ANTIMONOPOLISM AS A SYMPTOM OF AMERICAN POLITICAL DYSFUNCTION - Ramsi A. Woodcock (Теоретическая и прикладная юриспруденция)
Contemporary American interest in using antitrust law to address wealth inequality is a symptom of American political dysfunction rather than a reﬂection of any intellectual advance regarding the sources of inequality. Indeed, both the original American progressives of a century ago, as well as Thomas Piketty, whose work sparked contemporary intellectual interest in inequality, agree that inequality’s source is scarcity, rather than monopoly, and so will persist even in perfectly competitive markets. The only real solution is taxation, not a potentially destructive campaign of breakup. There are two causes of contemporary American antimonopolism. The ﬁrst is American anti-statism, which has closed off tax policy as a viable political solution to inequality, forcing scholars and activists to seek a secondor third-bestworkaroundinantitrustpolicy. Thesecondisthe Americanpress, whichisactivelypromotingantimonopolism as a way of ﬁghting back against Google and Facebook, two companies that have badly outcompeted the press for advertising dollars in recent years. Given these idiosyncratic roots of contemporary American antimonopolism, other jurisdictions seeking to address inequality may have little to gain from following the American example, particularly if taxation remains a viable policy option for them.